Ritual dan simbol dalam adat perkahwinan masyarakat Melayu Sekinchan, Selangor / Norhuda Salleh - Norhuda , Salleh (2017)
This study related to the rituals implemented by Malay society of Sekinchan, Selangor in marriage customs. There are four main objectives research which are to investigate the ritual processes in the implementation of Malay marriages in Kg. Seri Kedah, Sekinchan, and Selangor; to investigate the types of ritual symbols found in the marriage custom; to analyse the meaning of the ritual symbol; and assess the social values that contained in the ritual. This ethnographic based research, study the ritual practices in the marriage of the Malay community of Seri Kedah. Ethnographic interviews techniques involving respondents consists of Mak Andam, custom practitioners and religious persons comprising priests and kadi were used to collect the data. Besides, in-depth interviews with the brides and focus groups were carried out while in order to understand more and deepen the rituals in the marital customs of the community, observation techniques were also been widely used in this study. The observation technique is implemented during the engagement, wedding and reception customs. The findings show that there are three rituals processes that come along with Malay marital customs of Seri Kedah community which are the celebration ritual, prayer ritual and banquet ritual. Celebration ritual stands for the act of glorifying the guests that come in custom implementation. Prayer ritual shows the seek and hope toward Allah SWT for blessing the implemented marital custom and avoided from occurrence of bad things. Ritual of banquets as the last ritual is to ensure that the overall marriage customs achieved the perfection and the ultimate aim of it. The celebration of the ritual is performed as an inquiry, upholding customs, politeness, acceptance, honouring, getting acquainted, celebrating the guests, manners, identity exposure, connecting, strengthening affection and establishing social relationships. The prayer ritual provide as an importance of the responsibility, respect and hope, notification, acceptance, generosity, obedience to the leader and identity exposure. The ritual of banquet serves as a thanksgiving, strengthen relationships, gathering, donations, respecting guests, unity, generosity, warmth, acknowledging, reward and indicate the closing of the ceremony. The symbol analysis in this study show that there are three types of symbol being used which are object, verbal behaviour and non-verbal behaviour. Object symbol indicate the meaning of happiness, love, wealth, luxury, joy, residence, fertility, prosperity, kindness and holiness. Verbal behaviour display the gratitude, responsibility and sincerity while the non-verbal behaviour implies disclosure meaning of interconnected in making sure that the rituals are acquiring the true meaning. All the actions performed are to show their relationship with Allah SWT. This study explains that the rituals performed in the Malay marriage tradition of Seri Kedah have its own structure and social values. As to ensure the custom meet its achievement, the ritual needs to be done in the right order that had been set up appropriate with the social values in the community. The neglecting of the ritual practices resulted the imperfection of wedding custom. Without ritual, the custom is invalid in term of religious view and the community that practice it.